Lung function over the first 3 years of life in children with congenital diaphragmatic hernia. Issue 9 (10th July 2014) - Panitch, Howard B.; Weiner, Daniel J.; Feng, Rui; Perez, Myrza R.; Healy, Fiona; McDonough, Joseph M.; Rintoul, Natalie; Hedrick, Holly L.
Summary Objectives Infants with congenital diaphragmatic hernia (CDH) have variable degrees of pulmonary hypoplasia at birth. Few reports of lung function over the first years of life exist in this group of children. Hypothesis Pulmonary function abnormalities correlate with severity of neonatal disease and intensity of neonatal therapies needed. We also hypothesized that longitudinal measurements of lung function over the usual period of rapid lung growth would lend some insight into how the lung remodels in CDH infants. Methodology Ninety‐eight infants with CDH between 11 days and 44 months of age underwent pulmonary function testing (PFT) on 1–5 occasions using the raised volume rapid thoracic compression technique. Demographic data were also collected. Main Results Forced expiratory flows were below normal. Total lung capacity was normal, but residual volume and functional residual capacity were elevated. Children requiring patch closure, ECMO, or pulmonary vasodilators generally had lower lung functions at follow up. Additionally, longer duration of mechanical ventilation correlated with worse lung function. Conclusions Lung functions of survivors of CDH remain abnormal throughout the first 3 years of life. The degree of pulmonary function impairment correlated both with markers of the initial degree of pulmonary hypoplasia and the duration of mechanical ventilation. Understanding the relationship between the phenotypic presentation of CDH and the potential for subsequent lung growth could help refine both pre‐ and postnatal therapies to optimize lung growth in CDH infants. Pediatr Pulmonol. 2015; 50:896–907. © 2014 Wiley Periodicals, Inc.